1973
DOI: 10.1530/jrf.0.0340267
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Plasma Progesterone Concentration and Conception in Post-Partum Dairy Cows Maintained on Two Levels of Nutrition

Abstract: Summary. Fourteen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
4
8

Year Published

1978
1978
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(65 citation statements)
references
References 18 publications
(26 reference statements)
6
47
4
8
Order By: Relevance
“…Similarly the advantage of the progestagen treatments may be in the provision of increased plasma levels before the first cycle postpartum. This has been shown to increase conception rates (Ramirez-Godinez et al 1981) and agrees with the reported relationship between progesterone levels in the previous cycle and conception rate (Folman et al 1973;Corah et al 1974). …”
Section: Discussionsupporting
confidence: 87%
“…Similarly the advantage of the progestagen treatments may be in the provision of increased plasma levels before the first cycle postpartum. This has been shown to increase conception rates (Ramirez-Godinez et al 1981) and agrees with the reported relationship between progesterone levels in the previous cycle and conception rate (Folman et al 1973;Corah et al 1974). …”
Section: Discussionsupporting
confidence: 87%
“…The key role of greater P4 before AI on fertility of lactating dairy cows was recognized in early studies that compared fertile to non-fertile inseminations (Folman et al, 1973;Erb et al, 1976;Meisterling and Dailey, 1987). In addition, concentrations of P4 12 days before first AI had a positive relationship with conception rate at first AI in lactating Holstein and Jersey dairy cattle (Fonseca et al, 1983).…”
Section: Fertility In Dairy Cowsmentioning
confidence: 96%
“…They may involve effects on the hypothalamic-pituitary-ovarian axis through alterations to the LH pulse pattern and delays in the time of first ovulation after calving (Eldon et al, 1988) The effect may also be due to lower progesterone production and, consequently, lower conception rates at subsequent inseminations (Folman et al, 1973). In addition, increased urea concentration has been associated with a higher incidence of ovarian cysts (Ropstad and Refsdal, 1987).…”
Section: Discussionmentioning
confidence: 99%